2019
DOI: 10.3390/ma12132107
|View full text |Cite
|
Sign up to set email alerts
|

One Step Preparation of Peptide-Coated Gold Nanoparticles with Tunable Size

Abstract: Gold nanoparticles (AuNPs) made from self-assembling peptides have been used in many research fields and attracted a great deal of attention due to their high stability, biocompatibility and functionality. However, existing preparation methods for peptide-coated AuNPs are post-synthesis processes, which are complicated and time consuming. Therefore, a one-step preparation method for peptide-coated AuNPs is proposed here. The AuNPs obtained by this method exhibit good stability. Importantly, peptide-coated AuNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Furthermore, in terms of the pH stability, Jia et al show that CALNN conjugated Au NPs have stable colloidal properties for pH < 10. 76 For cysteamine, within the range of pH 4− 10, Au−cysteamine aggregates have been shown to be stable, with pH > 10 resulting in the deprotonation of the sulfur moiety, leading to destabilization of the product. 55,77 Notably, our in vitro experiments were performed at pH = 7.4, under stable pH conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in terms of the pH stability, Jia et al show that CALNN conjugated Au NPs have stable colloidal properties for pH < 10. 76 For cysteamine, within the range of pH 4− 10, Au−cysteamine aggregates have been shown to be stable, with pH > 10 resulting in the deprotonation of the sulfur moiety, leading to destabilization of the product. 55,77 Notably, our in vitro experiments were performed at pH = 7.4, under stable pH conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Self‐assembling short peptide conjugates have extensively been used in the production of hierarchical nanomaterial because of their versatility [28–30] . These organized materials when conjugated with bioactive metals, enhances the biocompatibility and cooperativity along with electromagnetic and optical properties of nanoparticles [29–32] . The coating of gold nanoparticles by designed peptide conjugates modulates the surface properties with specific biological function and reduces its side effects or toxicity [31–33] …”
Section: Figurementioning
confidence: 99%
“…[28][29][30] These organized materials when conjugated with bioactive metals, enhances the biocompatibility and cooperativity along with electromagnetic and optical properties of nanoparticles. [29][30][31][32] The coating of gold nanoparticles by designed peptide conjugates modulates the surface properties with specific biological function and reduces its side effects or toxicity. [31][32][33] Short peptide amphiphiles (sPAs) or Lipid-peptide conjugates exhibits a wide range of tightly packed self-assembling nanostructures such as spherical micelles, vesicles, fibers and ribbons, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Modifying the peptide sequence can contribute to peptide-AuNP synthesis without other additional linkers. 79 It had been reported that peptide-AuNP conjugates enhance the macrophage responses compared with sole peptide or AuNP. 80 Overexpression receptor αβ3 integrin was detected in the melanoma, glioblastoma and tumor vasculature.…”
Section: Gold Nanoparticles With Antibodies As Ligandsmentioning
confidence: 99%